Fuzzy Delphi method: designing a Tadabbur Al-Quran model in Arabic vocabulary learning for hearing-impaired Muslim adults and assisted with Augmented Reality technology - Ahmad Yusoff, Nabilah Fasihah; Abas, Ummu-Hani; Mat Ali, Ahmad Asyraf; Jaffar, Mohammad Najib; Md Noor, Mohamad Lukman Al Hakim; Abdul Hanid, Mohd Fadzil; Mohd Raus, Norakyairee (International Journal of Learning, Teaching and Educational Research, 2025)
This study aims to develop a Tadabbur al-Quran Model integrating Augmented Reality (AR) technology to enhance Arabic vocabulary learning for hearing-impaired Muslim adults. Conducted in collaboration with Persatuan Orang Pekak Islam Malaysia (PRISMA), a national NGO for the Deaf Muslim community, the research built upon a previous needs analysis findings to design a structured learning model. A questionnaire was developed to gather expert opinions on the model’s key components, focusing on Arabic vocabulary learning and AR’s potential in Quranic education. It was distributed to 10 experts in Arabic Education, Quranic and Special Needs Education, Educational Technology, and Model Development. The Fuzzy Delphi Method (FDM), using Fuzzy Delphi Analysis V1.5, analysed expert responses to refine the model. The findings showed consensus on all components, meeting three key Fuzzy criteria: the threshold value (d) was ≤ 0.2, the expert agreement percentage was ≥ 75%, and the Defuzzification (alpha cut) value was ≥ 0.5. This study contributes to fostering a more inclusive and effective learning environment for hearing-impaired learners by advocating for the integration of interactive and visually supportive tools, such as AR books and digital sign language resources, into Arabic vocabulary education.